PERSEPSI MAHASISWA TEKNIK SIPIL TERHADAP PROSES BELAJAR MENGAJAR SECARA ONLINE DI MASA PANDEMI COVID-19 - julia damayanti; Giraldi Kuswanda (INDONESIAN JOURNAL OF CONSTRUCTION ENGINEERING AND SUSTAINABLE DEVELOPMENT (CESD), 2020)
Online lectures have become the main means of academic learning during the COVID-19 pandemic. Without exception,this includes the students of the Civil Engineering study program, Faculty of Civil Engineering & Planning of Trisakti University who use online application facilites, such as google classroom, zoom and other media applications during online lectures. The purpose of this study is to determine the students’ perceptions of the online teaching and learning process during the COVID-19 pandemic. The population of this study are students of Civil Engineering program batch 2016 to 2020 who are registered as active for the odd semester of the 2020/2021 Academic Year. This research is a descriptive quantitative study and was conducted by using a simple random sampling method. The data collection techniques using interviews and questionnaires. The data analysis used to complete this research is the Likert scale survey method with a total sample of 247 student respondents.The results have shown that the majority of students of Civil Engineering as much as 90% attended online lectures using laptops.  As many as 90% of the students stated that they used the Zoom application to attend lectures via video conference. Technical issues that are often experienced by students during online lectures are dominated by unstable internet networks, this was stated by 75% of the students. About 66% of the students agree that online lectures can be accessed easily, only 34% of the students are satisfied with the online lecture mode, and on the latest rule of New Normal, 58% of the students agree that learning should be done by blended learning method.